A compositionally graded csPbBr x I 3-x Nanowires and controllable preparation method thereof
Patent Information
- Application Number
- CN202611035588.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]当异质结构中两种组分之间存在较大的能级差异时,会产生显著的能带补偿,进而影响电荷与载流子的快速传输
1. 传统的CsPbBr3纳米线通常由液相的自组装形成,制备的CsPbBr3纳米线一般含有较高的缺陷态密度;而化学气相沉积法需要的合成温度高,且无溶剂参与,制备的CsPbBr3纳米线表现出高的结晶度。以此CsPbBr3纳米线为基础制备的组分递变CsPbBrxI3-x纳米线具有高的结晶度、均匀的组分递变及渐变的宽谱发射。
Smart Images

Figure CN122977431A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor material preparation technology, specifically relating to a compositionally variable CsPbBr x I 3-x Nanowires and methods for their controllable preparation. Background Technology
[0002] The continuous miniaturization of silicon-based microelectronics has been the fundamental driving force behind the information technology revolution of the past half-century. This technology primarily relies on a top-down photolithography manufacturing strategy. However, as device sizes enter the single-digit nanometer scale, this strategy is rapidly approaching its physical and economic limits. Therefore, there is an urgent need to develop new manufacturing strategies to further advance science and technology. A bottom-up assembly strategy, which directly assembles artificially synthesized nanoscale building blocks into functional electronic devices and circuits, holds promise for endowing traditional top-down silicon-based microelectronics with new functions and characteristics, forming an effective complement.
[0003] Nanoscale building blocks are central to the bottom-up strategy. One-dimensional nanostructures, such as semiconductor nanowires and carbon nanotubes, can serve as both device units and essential interconnecting units for nanocircuits, making them ideal building blocks for assembling functional electronic devices from the bottom up. While traditional photolithography methods inevitably result in atomic-level roughness in device building blocks, current synthesis techniques can fabricate inorganic semiconductor nanowires with near-perfect crystal structures and atomically smooth surfaces, thus endowing them with excellent electronic properties. Furthermore, by precisely controlling key parameters in the fabrication process (such as temperature, pressure, and feed ratio), the chemical composition and doping concentration, diameter and length, and special structures such as kinks and multi-branching of inorganic semiconductor nanowires can be effectively controlled. These control methods can adjust or optimize their electronic properties, endowing devices with additional functions and broadening their application range.
[0004] Single-component nanowires, limited by their inherent electronic band structure and less-than-ideal carrier separation and transport characteristics, struggle to meet the increasingly diverse and sophisticated application demands. Constructing heterostructures on single nanowires not only effectively modulates charge and carrier transport but also integrates the advantages of different materials, significantly enhancing the performance of corresponding devices. Metal halide perovskites, due to their soft lattice properties, have become ideal candidate materials for fabricating heterojunction nanowires. Furthermore, these materials possess advantages such as high absorption coefficients, long carrier diffusion lengths, high defect tolerance, and low cost, making them highly suitable for the fabrication of high-performance, large-area optoelectronic devices. For example, Xia Hong et al. synthesized MAPbBr3-MAPbI3 lateral heterojunction nanowires using a template-assisted two-step solution method and fabricated a high-performance photodetector based on these nanowires, achieving responsivity and detectivity as high as 1207 AW. -1 and 2.78×1013 Jones, Huang Yong'an, and others prepared MAPbBr3-MAPbBr using anion exchange. 3-x I x Nanowire arrays, and corresponding photodetectors, can achieve broadband detection and ultrasensitive response. Ji Tae Kim and his collaborators used three-dimensional nanoprinting technology to achieve the free fabrication of halide perovskite nanowire heterojunctions with controllable morphology and composition. Among them, the (PEA)2PbI4 / (PEA)2SnI4 heterojunction nanowires can be used as self-powered photodetectors with responsivity and detectivity of 0.14 mA W. -1 and 4.3×10 10 Jones.
[0005] When there is a significant energy level difference between the two components in a heterostructure, significant band compensation occurs, which in turn affects the rapid transport of charge and charge carriers. Integrating compositionally graded materials into a single nanowire can construct a gradient band structure and optimize the energy level arrangement, thereby effectively mitigating the adverse effects of band compensation. Perovskite materials have low halide ion migration energies, making them prone to alloying during the fabrication of corresponding heterostructures or graded structures. Summary of the Invention
[0006] To address the above problems, this invention provides a compositional variation CsPbBr x I 3-x A method for the controllable preparation of CsPbBr3 nanowires and CsPbI3 quantum dot films was first synthesized using a high-quality out-of-plane grown CsPbBr3 nanowires. Then, the CsPbI3 quantum dot film was placed on the CsPbBr3 nanowires and annealed at 175 °C for 2 hours under a N2 atmosphere, resulting in controllable Br / I ion exchange and the generation of compositionally varying CsPbBr3 nanowires. x I 3-x Nanowires.
[0007] The present invention adopts the following technical solution: A component trend of CsPbBr x I 3-x Nanowires with the structural formula CsPbBr x I 3-x The component variation CsPbBr x I 3-x The proportion of Br in the nanowires gradually decreases along the axial direction, while the content of I gradually increases.
[0008] Furthermore, the compositional variation CsPbBr x I 3-x The nanowires are out-of-plane grown single-crystal nanowires.
[0009] Furthermore, the compositional variation CsPbBr x I 3-x The nanowires are 20-30 μm long and 300-500 nm in diameter.
[0010] Furthermore, the compositional variation CsPbBr x I 3-x The position of the emission peak along the axial direction of the nanowire gradually redshifts from 546 nm to 670 nm.
[0011] A component trend of CsPbBr x I 3-x A controllable preparation method for nanowires includes the following steps: S1, Synthesis of CsPbBr3 nanowires a. Weigh PbBr2 and CsBr according to the proportion, mix the weighed drugs evenly and place them in a quartz boat, and place the quartz boat in the center of the heating zone one of the dual-temperature zone tube furnace. b. The SiO2 / Si substrate was ultrasonically cleaned three times each with acetone, isopropanol and deionized water. After cleaning, Sn solution was dropped onto its surface. After drying, the substrate was placed at the front end of the second heating zone of the dual-temperature zone tube furnace. c. After placing the reagent and substrate in the designated position in the tube furnace, evacuate the system for 30 min, then introduce N2 at 150 sccm to help purge the air from the quartz tube and avoid adverse effects of oxygen and moisture on the experimental results. After 10 min of continuous venting, adjust the N2 flow rate to 50 sccm and simultaneously introduce H2 at a flow rate of 20 sccm to keep the furnace pressure stable at 5.2 Torr. d. Start the heating program: Heating zone one and heating zone two are heated to 440℃ and 310℃ respectively at heating rates of 22℃ / min and 15.5℃ / min, and held at these temperatures for 60 min. After the heating program is completed, the furnace body is allowed to cool naturally to room temperature, and out-of-plane CsPbBr3 nanowires can be obtained on the substrate surface. S2, Synthesis of CsPbI3 quantum dots a. Preparation of cesium oleate precursor: Cesium carbonate, octadecene, and oleic acid were added sequentially to a three-necked flask in proportion. The magnetic stirrer was turned on and the mechanical pump was started. The mixture was heated to 120 °C under vacuum. Then, the mixture was purged three times with high-purity nitrogen to remove moisture and oxygen from the system. After maintaining the temperature at 120 °C in a N2 environment for 1 hour, the temperature was raised to 150 °C and the reaction was carried out for half an hour. Finally, the mixture was cooled to room temperature and stored in a nitrogen environment for later use. b. CsPbI3 quantum dot synthesis: PbI2, oleic acid, oleylamine and octadecene were added to a three-necked flask in proportion. The magnetic stirrer was turned on and the mechanical pump was started. The mixture was heated to 120 °C under vacuum. Then, the gas was replaced three times with high-purity nitrogen to remove moisture and oxygen from the system. After holding the mixture at 120 °C in N2 environment for 1 hour, the temperature was raised to 180 °C. The cesium oleate precursor solution heated to 100 °C was quickly injected into the reaction solution. After the mixture reacted for 5 seconds, it was quickly transferred to an ice-water mixture for cooling. c. Purification and modification: Ethyl acetate was added to the cooled solution and mixed evenly. The mixture was centrifuged at 8000 rpm for 5 min and then dispersed in toluene solution. Then, toluene solution of p-methylphenethylamine and N'N-dimethylformamide / toluene solution of p-toluenesulfonic acid were added to the solution in sequence. After stirring at room temperature for 10 min, ethyl acetate was added. After centrifugation under the same conditions twice, the mixture was redispersed in n-octane to obtain CsPbI3 quantum dot solution. d. Preparation of CsPbI3 quantum dot thin films: CsPbI3 quantum dot solution was dropped onto a SiO2 / Si substrate, spin-coated at 2000 rpm for 2 min, and dried at room temperature for 5 min to obtain CsPbI3 quantum dot thin films; S3, Synthesis Composition Trends CsPbBr x I 3-x nanowires CsPbI3 quantum dot films were placed on CsPbBr3 nanowires and then placed in the center of the heating zone of a tube furnace. A vacuum was applied for 30 minutes, followed by the introduction of 150 sccm of N2 to purge air from the quartz tube and prevent air from affecting the experimental results. After 10 minutes, the N2 flow rate was adjusted to 200 sccm, and the vacuum valve was adjusted to stabilize the furnace pressure at atmospheric pressure. The heating program was then started, and the temperature was increased to 175 °C at a rate of 15 °C / min. This temperature was maintained for 2 hours, after which the heating program was stopped, and the CsPbBr3 nanowires were allowed to cool naturally to room temperature to obtain the compositionally graded CsPbBr3 nanowires. x I 3-x Nanowires.
[0012] Furthermore, in S1, the molar ratio of PbBr2 to CsBr is 1:2.
[0013] Further, in S1, the concentration of the Sn solution is 0.05 mg / mL, and the solvent of the Sn solution is ethanol.
[0014] Further, in step a of S2, the ratio of cesium carbonate, octadecene, and oleic acid is 0.625g: 25mL: 2.5mL.
[0015] Further, in step b of S2, the ratio of the amounts of PbI2, oleic acid, oleylamine, octadecene and cesium oleate precursor solution is 90 mg: 0.5 mL: 0.5 mL: 5 mL: 0.4 mL.
[0016] Furthermore, in step c of S2, the amount of ethyl acetate added to the cooled solution is 12 mL; The volume of the toluene solution used is 6 mL; the concentration of the toluene solution of p-methylphenethylamine is 0.3 M, and the volume is 0.15 mL. The concentration of the p-toluenesulfonic acid N'N-dimethylformamide / toluene solution is 0.3M, the volume is 0.15mL, and the volume ratio of N'N-dimethylformamide / toluene is 1:9; After stirring at room temperature for 10 min, the amount of ethyl acetate added was 12 mL. The amount of n-octane used is 1 mL.
[0017] The beneficial effects of this invention are as follows: 1. Traditional CsPbBr3 nanowires are typically formed through self-assembly in the liquid phase, resulting in nanowires with a high defect state density. In contrast, chemical vapor deposition (CVD) requires high synthesis temperatures and involves no solvent, leading to CsPbBr3 nanowires exhibiting high crystallinity. Based on these CsPbBr3 nanowires, compositionally graded CsPbBr3 nanowires were prepared... x I 3-x Nanowires exhibit high crystallinity, uniform compositional variation, and gradually increasing broadband emission.
[0018] 2. Perovskites exhibit low halide ion migration energies, requiring existing techniques to perform additional treatments on the iodine source (such as converting the synthesized black-phase CsPbI3 to a yellow phase) to modulate the halide ion exchange kinetics. However, the CsPbI3 quantum dots synthesized in this invention possess stable, strongly bonded ligands on their surface, thus allowing the iodine source to effectively regulate the ion exchange rate with CsPbBr3 nanowires in the contact region. Furthermore, the high-quality CsPbBr3 nanowires synthesized in this invention also ensure controllable iodine ion diffusion and exchange within the nanowires.
[0019] 3. Existing technology composition trends: CsPbBr x I 3-xThe synthesis of nanowires requires the additional transfer of CsPbBr3 nanowires and an iodine source to a new substrate. This process necessitates precise end-to-end contact between the two for controlled anion exchange. This increases the difficulty and complexity of the operation and is not conducive to large-scale preparation. However, the CsPbBr3 nanowires prepared in this invention exhibit out-of-plane growth characteristics. Therefore, simply placing the iodine source above the CsPbBr3 nanowires allows for effective anion exchange through the contact region at the nanowire's end. Thus, this invention enables the large-scale preparation of compositionally graded CsPbBr3 nanowires. x I 3-x Nanowires.
[0020] 4. This invention is also applicable to the controllable fabrication of semiconductor nanowires with varying compositions. Attached Figure Description
[0021] Figure 1 A schematic diagram of the apparatus for synthesizing CsPbBr3 nanowires; Figure 2 Low-magnification SEM image of CsPbBr3 nanowires deposited on a SiO2 / Si substrate; Figure 3 High-magnification SEM image of CsPbBr3 nanowires deposited on a SiO2 / Si substrate; Figure 4 XRD pattern of CsPbBr3 nanowires; Figure 5 Transmission electron microscopy image of CsPbBr3 nanowires; Figure 6 2D EDX elemental mapping image of CsPbBr3 nanowires; Figure 7 for Figure 6 EDX spectrum at position 1 in the middle; Figure 8 for Figure 6 EDX spectrum at position 2 in the middle; Figure 9 for Figure 6 EDX spectrum at position 3 in the middle; Figure 10 for Figure 6 A comparison chart of the abundance ratios of Br, I, and Pb elements at positions 1, 2, and 3 in the middle; Figure 11 Dark-field emission pattern of the newly synthesized CsPbBr3 nanowires; Figure 12 Dark-field emission pattern of a dispersed single CsPbBr3 nanowire; Figure 13 for Figure 12 PL spectra at positions 1-5 in the middle; Figure 14This is a transmission electron microscope image of the newly synthesized CsPbI3 quantum dots. Figure 15 Transmission electron microscopy image of the modified CsPbI3 quantum dots; Figure 16 The images show the XRD patterns of the newly synthesized CsPbI3 quantum dots and the modified CsPbI3 quantum dots. Figure 17 The PL spectra of the newly synthesized CsPbI3 quantum dots and the modified CsPbI3 quantum dots are shown. Figure 18 For the compositional variation CsPbBr x I 3-x Schematic diagram of the nanowire synthesis apparatus; Figure 19 For the compositional variation CsPbBr x I 3-x Dark-field emission pattern of nanowires; Figure 20 For the compositional variation CsPbBr x I 3-x Schematic diagram of the composition and band structure of nanowires; Figure 21 For single-component trending CsPbBr x I 3-x Dark field emission images of nanowires and corresponding PL spectra at six positions along the nanowire axis; Figure 22 For single-component trending CsPbBr x I 3-x 2D EDX elemental mapping of nanowires; Figure 23 for Figure 22 A schematic diagram showing the changes in Pb, Br, and I content at eight locations along the nanowire axis; Figure 24 For single-component trending CsPbBr x I 3-x Low-magnification TEM images of the nanowires and high-magnification TEM images at six locations along the nanowire axis. Detailed Implementation
[0022] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, facilitating a better understanding and utilization of the present invention by those skilled in the art, and are not intended to limit the scope of protection of the present invention.
[0023] A component trend of CsPbBr x I 3-x A method for controllable fabrication of nanowires includes the following steps: (1) Step 1: Synthesis of CsPbBr3 nanowires First, weigh 50 mg of PbBr2 and 58 mg of CsBr at a molar ratio of 1:2. After thoroughly mixing the weighed drugs, place them in a quartz boat and position the quartz boat at the center of the heating zone one of the dual-zone tube furnace.
[0024] The SiO2 / Si substrate was ultrasonically cleaned three times each with acetone, isopropanol, and deionized water. After cleaning, a Sn solution (0.05 mg / mL, ethanol) was dropped onto its surface. After drying, the substrate was placed at the front end of the second heating zone of a dual-temperature zone tube furnace.
[0025] After placing the aforementioned reagents and substrate in the designated positions within the tube furnace, the system was evacuated for 30 minutes. Subsequently, 150 sccm of N2 was introduced to help purge the air from the quartz tube, preventing oxygen and moisture from adversely affecting the experimental results. After 10 minutes of aeration, the N2 flow rate was adjusted to 50 sccm, while H2 was introduced at a flow rate of 20 sccm to maintain a stable furnace pressure of 5.2 Torr.
[0026] The heating program was initiated: Temperature zones one and two were heated to 440 °C and 310 °C respectively at heating rates of 22 °C / min and 15.5 °C / min, and held at these temperatures for 60 min. After the heating program was completed, the furnace was allowed to cool naturally to room temperature, and out-of-plane CsPbBr3 nanowires were obtained on the substrate surface.
[0027] (2) Step 2: Synthesis of CsPbI3 quantum dots The synthesis of CsPbI3 quantum dots is based on the hot-pouring method, and the detailed preparation process is as follows: ① Preparation of cesium oleate precursor: 0.625 g of cesium carbonate, 25 ml of octadecene, and 2.5 ml of oleic acid were sequentially added to a 50 ml three-necked flask. A magnetic stirrer was turned on, and a mechanical pump was started. The mixture was heated to 120 °C under vacuum. Then, the mixture was purged three times with high-purity nitrogen to remove moisture and oxygen from the system. After maintaining the temperature at 120 °C in a N2 environment for 1 hour, the temperature was increased to 150 °C, and the reaction was allowed to proceed for half an hour. Finally, the mixture was cooled to room temperature and stored under a nitrogen atmosphere for later use.
[0028] ②CsPbI3 quantum dot synthesis: 90 mg PbI2, 0.5 mL oleic acid, 0.5 mL oleylamine, and 5 mL octadecene were sequentially added to a 50 mL three-necked flask. The same procedure as for cesium carbonate preparation was used to remove moisture and oxygen from the mixture. After incubating at 120 °C in a N2 environment for 1 hour, the temperature was raised to 180 °C, and 0.4 mL of the precursor solution heated to 100 °C was rapidly injected into the reaction solution. After the mixture reacted for 5 seconds, it was quickly transferred to an ice-water mixture for cooling.
[0029] ③ Purification and Modification: Add 12 mL of ethyl acetate to the cooled solution and mix thoroughly. Centrifuge at 8000 rpm for 5 min, then disperse in 6 mL of toluene solution. Next, add 0.15 mL of a toluene solution of p-methylphenethylamine (0.3 M) and 0.15 mL of a mixed solution of p-toluenesulfonic acid in N'N-dimethylformamide / toluene (volume ratio 1:9) (0.3 M) to the solution sequentially. After stirring at room temperature for 10 min, add 12 mL of ethyl acetate, centrifuge twice under the same conditions, and redisperse in 1 mL of n-octane.
[0030] ④ Preparation of CsPbI3 quantum dot thin film: The CsPbI3 quantum dot solution prepared above was dropped onto a SiO2 / Si substrate, spin-coated at 2000 rpm for 2 min, and dried at room temperature for 5 min to obtain CsPbI3 quantum dot thin film.
[0031] (3) Step 3: Synthesis of CsPbBr x I 3-x nanowires CsPbI3 quantum dot films were placed on CsPbBr3 nanowires and positioned in the center of the heating zone of a tube furnace. After evacuation for 30 minutes, 150 sccm of N2 was introduced to purge air from the quartz tube, preventing air from affecting the experimental results. After 10 minutes, the N2 flow rate was adjusted to 200 sccm, and the vacuum valve was adjusted to stabilize the furnace pressure at atmospheric pressure. The heating program was started, and the temperature was increased to 175 °C at a rate of 15 °C / min. This temperature was maintained for 2 hours, after which the heating program was stopped, and the film was allowed to cool naturally to room temperature to obtain the compositionally graded CsPbBr3 nanowires. x I 3-x Nanowires.
[0032] Figure 1 This is a schematic diagram of the CsPbBr3 nanowire synthesis device. The drug is placed upstream and the substrate is placed downstream. In the experiment, the volatile drug is deposited on the substrate at high temperature using a carrier gas.
[0033] Figure 2 and Figure 3The images show low-magnification and high-magnification SEM images of CsPbBr3 nanowires grown on SiO2 / Si substrates. As can be seen from the images, the CsPbBr3 nanowires exhibit a smooth and regular morphology, indicating that the nanowires possess high crystal quality and have no obvious defect states.
[0034] Figure 4 The image shows the XRD pattern of CsPbBr3 nanowires. The XRD results indicate that the synthesized material is CsPbBr3 (the diffraction peaks are consistent with the standard colorimetric card). Furthermore, the high intensity and narrow full width at half maximum (FWHM) of the diffraction peaks indicate that the synthesized CsPbBr3 nanowires possess high crystallinity. Figure 5 The TEM results further confirm this view.
[0035] Figures 6-10 This indicates that the CsPbBr3 nanowires contain only three elements: Cs, Pb, and Br, and these three elements are uniformly distributed along the axial direction in a ratio of 1:1:3.
[0036] Figures 11 to 13 The optical properties of the synthesized CsPbBr3 nanowires were tested. Figure 11 As can be seen, the newly synthesized CsPbBr3 nanowires exhibit bright green fluorescence under 405 nm laser irradiation. Figure 13 The photoluminescence (PL) spectra of a single CsPbBr3 nanowire were measured at five positions along the axial direction. The PL spectra at the five points maintained nearly consistent emission peak positions (525 nm) and intensities, and no additional emission peaks were observed. These results further demonstrate that the synthesized CsPbBr3 nanowires possess high crystal quality, excellent luminescent properties, and a low defect state density.
[0037] Figures 14-17 The morphology, structure, and PL spectra of freshly synthesized and modified CsPbI3 quantum dots were measured separately. Figure 14 and Figure 15 It can be seen that the modified CsPbI3 quantum dots have a more regular morphology, indicating that their surface ligands have higher stability, which can effectively regulate the migration dynamics of iodine ions. Furthermore, the regular morphology makes it easier to form a flat film, which is beneficial for uniform ion exchange with CsPbBr3 nanowires. Figure 16 XRD diffraction patterns indicate that the modified CsPbI3 quantum dot structure is more stable and less prone to phase transitions. Figure 17 As shown, the modified CsPbI3 quantum dots exhibit higher luminescence intensity, indicating that the modified CsPbI3 quantum dots have a lower defect state density, which can suppress the rapid migration of iodine ions and avoid the formation of alloy nanowires.
[0038] Figure 18 The compositional trends of CsPbBr were shown. x I3-x Schematic diagram of the nanowire synthesis apparatus. A CsPbI3 quantum dot film is placed on top of out-of-plane grown CsPbBr3 nanowires. The sample is heated in a tube furnace under ambient pressure and N2 atmosphere for 2 hours (175 °C). After cooling to room temperature, the CsPbBr3 nanowires are transformed into compositionally graded CsPbBr3 nanowires. x I 3-x Nanowires. From Figure 19 As can be seen, the composition of the synthesized CsPbBr... x I 3-x The nanowires appear red at the top and gradually transition to green at the bottom.
[0039] Figures 20-24 The compositional trends of CsPbBr were characterized respectively. x I 3-x Optical properties, composition and structure of nanowires. Figure 20 For the compositional variation CsPbBr x I 3-x Schematic diagram of the composition and band structure of nanowires. The compositional changes (CsPbBr) as the Br content gradually decreases. x I 3-x The band gap of the nanowires also gradually decreases. Figure 21 The single-component trend of CsPbBr was shown. x I 3-x Dark-field emission optical pattern of nanowire. The PL spectrum was measured at six positions along the axis of the nanowire. The results showed that the PL spectrum gradually redshifted from 546 nm to 670 nm, indicating that the band gap of the nanowire gradually decreased along the axis. Figure 22 2D EDX elemental mapping spectrum illustrates the compositional trends of CsPbBr x I 3-x The Br content of the nanowires gradually decreases from left to right along the axis, while the corresponding I content gradually increases. Figure 23 Tested separately Figure 22 EDX spectra of eight positions in the medium-sized nanowires showed that the proportion of Br gradually decreased from 54.16% to 16.46%, the proportion of iodine increased from 5.9% to 41.16%, while the proportion of Pb remained relatively stable (around 20%). Figure 24 The compositional trends of CsPbBr are shown in the figures. x I 3-x Low-magnification and high-magnification TEM images of the nanowires. The lattice fringes in the images gradually increase from 0.292 nm to 0.312 nm, a result consistent with CsPbBr. x I 3-xThe (200) crystal plane, and the increasing lattice fringes are due to the gradual replacement of smaller atomic radius Br by larger atomic radius I. Combining the above results, the compositional variation of CsPbBr... x I 3-x The nanowire exhibits varying halogen content and band structure.
[0040] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of the present invention.
Claims
1. A component trend of CsPbBr x I 3-x Nanowires, characterized by: The nanowires have the structural formula CsPbBr x I 3-x The component variation CsPbBr x I 3-x The proportion of Br in the nanowires gradually decreases along the axial direction, while the content of I gradually increases.
2. The component-gradient CsPbBr according to claim 1 x I 3-x Nanowires, characterized by: The component progression CsPbBr x I 3-x The nanowires are out-of-plane grown single-crystal nanowires.
3. A compositional variation CsPbBr according to claim 1 x I 3-x Nanowires, characterized by: The component progression CsPbBr x I 3-x The nanowires are 20-30 μm long and 300-500 nm in diameter.
4. A compositional variation CsPbBr according to claim 1 x I 3-x Nanowires, characterized by: The component progression CsPbBr x I 3-x The position of the emission peak along the axial direction of the nanowire gradually redshifts from 546 nm to 670 nm.
5. A compositional variation CsPbBr as described in claim 1 x I 3-x A method for controllable fabrication of nanowires, characterized by: Includes the following steps: S1, Synthesis of CsPbBr3 nanowires a. Weigh PbBr2 and CsBr according to the proportion, mix the weighed drugs evenly and place them in a quartz boat, and place the quartz boat in the center of the heating zone one of the dual-temperature zone tube furnace. b. The SiO2 / Si substrate was ultrasonically cleaned three times each with acetone, isopropanol and deionized water. After cleaning, Sn solution was dropped onto its surface. After drying, the substrate was placed at the front end of the second heating zone of the dual-temperature zone tube furnace. c. After placing the drug and substrate in the designated position in the tube furnace, evacuate the system for 30 min, then introduce 150 sccm of N2 to help purge the air from the quartz tube. After 10 min of continuous evacuation, adjust the N2 flow rate to 50 sccm and simultaneously introduce H2 at a flow rate of 20 sccm to keep the furnace pressure stable at 5.2 Torr. d. Start the heating program: Heating zone one and heating zone two are heated to 440℃ and 310℃ respectively at heating rates of 22℃ / min and 15.5℃ / min, and held at these temperatures for 60 min. After the heating program is completed, the furnace body is allowed to cool naturally to room temperature, and out-of-plane CsPbBr3 nanowires can be obtained on the substrate surface. S2, Synthesis of CsPbI3 quantum dots a. Preparation of cesium oleate precursor: Cesium carbonate, octadecene and oleic acid were added to a three-necked flask in proportion. The magnetic stirrer was turned on and the mechanical pump was started. The mixture was heated to 120 °C under vacuum. Then, the mixture was purged three times with high-purity nitrogen to remove moisture and oxygen from the system. After holding the mixture at 120 °C in a N2 environment for 1 hour, the temperature was raised to 150 °C and the reaction was carried out for half an hour. Finally, the mixture was cooled to room temperature and stored in a nitrogen environment for later use. b. CsPbI3 quantum dot synthesis: PbI2, oleic acid, oleylamine and octadecene were added to a three-necked flask in proportion. The magnetic stirrer was turned on and the mechanical pump was started. The mixture was heated to 120 °C under vacuum. Then, the gas was replaced three times with high-purity nitrogen to remove moisture and oxygen from the system. After holding the mixture at 120 °C in N2 environment for 1 hour, the temperature was raised to 180 °C. The cesium oleate precursor solution heated to 100 °C was quickly injected into the reaction solution. After the mixture reacted for 5 seconds, it was quickly transferred to an ice-water mixture for cooling. c. Purification and modification: Ethyl acetate was added to the cooled solution and mixed evenly. The mixture was centrifuged at 8000 rpm for 5 min and then dispersed in toluene solution. Then, toluene solution of p-methylphenethylamine and N'N-dimethylformamide / toluene solution of p-toluenesulfonic acid were added to the solution in sequence. After stirring at room temperature for 10 min, ethyl acetate was added. After centrifugation under the same conditions twice, the mixture was redispersed in n-octane to obtain CsPbI3 quantum dot solution. d. Preparation of CsPbI3 quantum dot thin films: CsPbI3 quantum dot solution was dropped onto a SiO2 / Si substrate, spin-coated at 2000 rpm for 2 min, and dried at room temperature for 5 min to obtain CsPbI3 quantum dot thin films; S3, Synthesis Composition Trends CsPbBr x I 3-x nanowires CsPbI3 quantum dot films were placed on CsPbBr3 nanowires and then placed in the center of the heating zone of a tube furnace. After evacuation for 30 minutes, 150 sccm of N2 was introduced to help purge the air from the quartz tube for 10 minutes. The N2 flow rate was then adjusted to 200 sccm, and the vacuum valve was adjusted to stabilize the furnace pressure at atmospheric pressure. The heating program was then started, and the temperature was increased to 175 °C at a rate of 15 °C / min. This temperature was maintained for 2 hours, after which the heating program was ended. After natural cooling to room temperature, the compositionally graded CsPbBr3 nanowires were obtained. x I 3-x Nanowires.
6. A compositional variation CsPbBr according to claim 5 x I 3-x A method for controllable fabrication of nanowires, characterized by: In S1, the molar ratio of PbBr2 to CsBr is 1:
2.
7. A compositional variation CsPbBr according to claim 5 x I 3-x A method for controllable fabrication of nanowires, characterized by: In S1, the concentration of the Sn solution is 0.05 mg / mL, and the solvent of the Sn solution is ethanol.
8. A compositional variation CsPbBr according to claim 5 x I 3-x A method for controllable fabrication of nanowires, characterized by: In step a of S2, the ratio of cesium carbonate, octadecene, and oleic acid is 0.625g: 25mL: 2.5mL.
9. A compositional variation CsPbBr according to claim 5 x I 3-x A method for controllable fabrication of nanowires, characterized by: In step b of S2, the ratio of the amounts of PbI2, oleic acid, oleylamine, octadecene and cesium oleate precursor solution is 90 mg: 0.5 mL: 0.5 mL: 5 mL: 0.4 mL.
10. A compositional variation CsPbBr according to claim 5 x I 3-x A method for controllable fabrication of nanowires, characterized by: In step c of S2, the amount of ethyl acetate added to the cooled solution is 12 mL; The volume of the toluene solution used is 6 mL; the concentration of the toluene solution of p-methylphenethylamine is 0.3 M, and the volume is 0.15 mL. The concentration of the p-toluenesulfonic acid N'N-dimethylformamide / toluene solution is 0.3M, the volume is 0.15mL, and the volume ratio of N'N-dimethylformamide / toluene is 1:9; After stirring at room temperature for 10 min, the amount of ethyl acetate added was 12 mL. The amount of n-octane used is 1 mL.